Resveratrol ameliorates maternal separation-induced anxiety- and depression-like behaviors and reduces Sirt1-NF-kB signaling-mediated neuroinflammation - Wei, Ru-Meng; Zhang, Yue-Ming; Feng, Yi-Zhou; Zhang, Kai-Xuan; Zhang, Jing-Ya; Chen, Jing; Luo, Bao-Ling; Li, Xue-Yan; Chen, Gui-Hai (Frontiers in Behavioral Neuroscience, 2023)
Maternal separation in early life has a detrimental effect on the physiological and biochemical functions of the brains of offspring and can lead to anxiety- and depression-like behaviors later in life. Resveratrol possesses a variety of pharmacological properties, including anti-inflammatory, anxiolytic, and antidepressive effects. In rodents, resveratrol can attenuate anxiety- and depression-like behaviors induced by chronic unpredictable mild stress, estrogen deficiency, and lipopolysaccharide. However, whether resveratrol administration during adolescence can counteract these behaviors when they result from maternal separation is unknown. In this study, male C57BL/6J mice were separated from their mothers for 4 h per day from postnatal day 2 (PND 2) to PND 21; starting on PND 61, resveratrol was administered intraperitoneally at 40 mg/(kg/day-1) for 4 weeks. At 3 months of age, anxiety and depression-like behaviors were assessed in the male offspring using a series of tasks consisting of an open field test, an elevated plus maze test, a forced swimming test, and a tail suspension test. The hippocampal levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha (TNF-α) were measured by ELISA, while those of sirtuin 1 (Sirt1) and nuclear factor kappa B (NF-κB) p65 were determined by western blotting and PCR. The results showed that maternal separation led to increased anxiety- and depression-like behaviors, enhanced the levels of pro-inflammatory cytokines, and downregulated the Sirt1/NF-κB signaling pathway in the male offspring; however, these effects could be reversed by treatment with resveratrol. Our findings suggested that resveratrol can ameliorate inflammation and anxiety- and depression-like behaviors induced by maternal separation via the activation of the Sirt1/NF-κB pathway.